FRI0042 CERTOLIZUMAB PEGOL EFFECTIVENESS IN WOMEN OF CHILDBEARING AGE WITH RHEUMATOID ARTHRITIS: RETROSPECTIVE ANALYSIS OF AN INTERNATIONAL MULTICENTRE COHORT. (June 2019) - Favalli, Ennio Giulio; Becciolini, Andrea; Caporali, Roberto; Puttini, Piercarlo Sarzi; Gorla, Roberto; Ionescu, R; Rednic, S; Balanescu, A; Rezus, E; Mogosan, C; Codreanu, Catalin
Abstract : Background: Even though certolizumab pegol (CZP) has been licensed for the treatment of rheumatoid arthritis (RA) a long time ago, observational data in real-life settings are still lacking. Moreover, recent data on the lack of transplacental passage (1) make CZP particularly appealing for the treatment of RA women with a desire of pregnancy. Objectives: To evaluate in a real-life international cohort the frequency of use, the clinical response, and the retention rate of CZP in RA women of childbearing age. Methods: Data were retrospectively extracted from the Italian LORHEN and the Romanian Registry of Rheumatic Diseases (RRBR) registries, which include all RA patients treated with CZP between December 2010 and October 2018. The analysis was limited to women who received CZP as first-line biologic agent. The study population was stratified according to childbearing age (18-49 versus >49 years). The 6-, 12- and 24-month clinical response was evaluated as the proportion of patients achieving Disease Activity Score 28 (DAS28) remission and compared between the subgroups by a chi-squared test. The 5-year retention rate was calculated by the Kaplan-Meier method and compared between the subgroups by log-rank test. Results: The whole cohort included 630 RA patients treated with CZP. According to the inclusion criteria, the study population consisted of 308 female RA patients (mean [± standard deviation, SD] age 54.2±12.1 years; mean disease duration 8.7±8.4 years; baseline DAS28 5.25±1.72, positive anti-citrullinated peptide antibody 161/254 [63.4%], positive rheumatoid factor 213/297 [71.7%]). Apart from mean age (39.6±6.6 vs 60.8±7.2, respectively; p<0.001), no other significant differences in baseline characteristics between the childbearing (n=97, 31.5%) and non-childbearing age (n=211, 68.5%) groups were observed. In the overall population, DAS28 remission was achieved by 29.9%, 42.1%, and 39.7% of patients at 6, 12, and 24 months, respectively. This proportion was significantly higher in childbearing compared with non-childbearing women at each timepoint (39.4% vs 25.4, p=0.02 at 6 months; 52.8% vs 37%, p=0.014 at 12 months; 52% vs 34.2%, p=0.014 at 24 months). The overall 5-year retention rate was 37.1%, with a higher (but not statistically significant) persistence in the childbearing versus non-childbearing subgroup (55.1% vs 33.4%, p=0.177). In the whole cohort the most frequent reason for withdrawal was inefficacy (60.9%), whereas only 10.9% of patients discontinued the drug because of adverse events. Conclusion: In our real-life data, CZP showed a high remission rate with a good safety profile and high persistence on treatment over 5 years. These findings were even more favorable during the childbearing age, supporting the use of CZP in RA women with a desire for pregnancy. Reference: [1] Mariette X, Förger F, Abraham B, et al. Lack of placental transfer of certolizumab pegol during pregnancy: results from CRIB, a prospective, postmarketing, pharmacokinetic study. Ann Rheum Dis. 2018;77:228-33. Disclosure of Interests: Ennio Giulio Favalli: None declared, Andrea Becciolini: None declared, Roberto Caporali Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Roche, Genzyme, Lilly, MSD, Pfizer, UCB, Piercarlo Sarzi Puttini: None declared, Roberto Gorla: None declared, R Ionescu: None declared, S Rednic: None declared, A Balanescu: None declared, E Rezus: None declared, C Mogosan: None declared, Catalin Codreanu: None declared